Die Trennung von Staat und Kirche: jüngere Entwicklungen in Frankreich im Vergleich zum deutschen Kooperationsmodell - Wick, Volker (Jus Ecclesiasticum, 2007)
In a comparison with the German cooperation model, Volker Wick examines how the French government deals with the current religious challenges, such as for example the so-called problems with sects or with Islam.